What Do We Talk About When We Talk About Others? Evidence for the Primacy of the Horizontal Dimension of Social Evaluation in Workplace Gossip - Elena Martinescu; Kim Peters; Bianca Beersma (International Review of Social Psychology, 2022)
In this paper we describe a bottom-up exploration of the social evaluations that emerge from the gossip people hear about others in a workplace context. We used the Dual Perspective Model (DPM: Abele & Wojciszke, 2007, 2014, 2018) to code open-format gossip stories provided by 522 participants for evaluations of gossip targets’ warmth and morality (i.e., communion) and competence and assertiveness (i.e., agency). We additionally coded evaluations of work-effort, self-control, and stress, as well as the gossip topic. Our analysis revealed that communion facet evaluations were more frequent than agency facet evaluations. Additionally, gossip was predominantly negative, reflecting the fact that evaluations usually conveyed information about low warmth, morality and competence; assertiveness was an exception, with high evaluations more common than low. These negative evaluations were most frequently contained in gossip about the negative character of the target and work-related norm transgressions. Our analysis further revealed distinct patterns of co-occurrence for the DPM facets, providing further evidence of the utility of distinguishing not only between the major dimensions of social evaluation, but also their facets. This research provides new insights regarding the variety, prevalence, and valence of social evaluations that emerge from workplace gossip. Most important in the present context, it shows the usefulness of the DPM facets in understanding the content of gossip.